Why does library holding format really matter for book impact assessment?: Modelling the relationship between citations and altmetrics with print and electronic holdings - Maleki Ashraf (Springer Nature, 2022)
Scholarly books are important outputs in some fields and their many publishing formats seem to introduce opportunities to scrutinize their impact. As there is a growing interest in the publisher-enforced massive collection of ebooks in libraries in the past decade, this study examined how this influences the relationship that library print holdings (LPH), library electronic holdings (LEH) and total library holdings (TLH) have with other metrics. As a follow up study to a previous research on OCLC library holdings, the relationship between library holdings and twelve other metrics including Scopus Citations, Google Books (GB) Citations, Goodreads engagements, and Altmetric indicators were examined for 119,794 Scopus-indexed book titles across 26 fields. Present study confirms the weak correlation levels observed between TLH and other indicators in previous studies and contributes additional evidence that print holdings can moderately reflect research, educational and online impact of books consistently more efficient than eholdings and total holdings across fields and over time, except for Mendeley for which eholdings slightly prevailed. Regression models indicated that along with other dimensions, Google Books Citations frequently best explained LPH (in 14 out of 26 fields), whereas Goodreads User counts were weak, but the best predictor of both LEH and TLH (in 15 fields out of 26), suggesting significant association of eholdings with online uptake of books. Overall, findings suggest that inclusion of eholdings overrides the more impactful counts of print holdings in Total Library Holdings metric and therefore undermines the statistical results, whilst print holdings has both statistically and theoretically promising underlying assumptions for prediction of impact of books and shows greater promise than the general Library Holding metric for book impact assessment. Thus, there is a need for a distinction between print and electronic holding counts to be made, otherwise total library holding data need to be interpreted with caution.